Child Maltreatment and Breast Cancer Survivors: Social Support Makes a Difference for Quality of Life, Fatigue, and Cancer Stress - Fagundes, Christopher P. (2012)
PURPOSE: To identify how child maltreatment is associated with quality of life (QOL) among breast cancer survivors. PATIENTS AND METHODS: One hundred and thirty two women who had completed treatment for stage 0-IIIA breast cancer within the past two years (except for tamoxifen/aromatase inhibitors) and were at least two months post surgery, radiation, or chemotherapy completed questionnaires including the Childhood Trauma Questionnaire, the Impact of Events Scale, the Multidimensional Fatigue Symptom Inventory-Short Form (MFSI-SF), and the Fact-B breast cancer quality of life questionnaire. RESULTS: Women who were abused or neglected as children reported more cancer-related psychological distress, more fatigue, and poorer physical, emotional, functional, and breast cancer specific well-being after treatment. These relations were partially explained by the fact that breast cancer survivors reported receiving less support as adults. CONCLUSION: The findings suggest that child maltreatment is an important predictor of QOL among breast cancer survivors. One reason why this association exists is because those who are maltreated as children report less support as adults. A better understanding of how child maltreatment contributes to breast cancer survivor QOL will help in tailoring and therefore enhancing the efficacy of interventions aimed at improving QOL.